Agreement between the categorization of isolates of Aeromonas salmonicida and Yersinia ruckeri by disc diffusion and MIC tests performed at 22℃. Issue 7 (22nd March 2021) - Baron, Sandrine; Larvor, Emeline; Jouy, Eric; Kempf, Isabelle; Le Bouquin, Sophie; Chauvin, Claire; Boitard, Pierre‐Marie; Jamin, Matthieu; Le Breton, Alain; Thuillier, Benoit; Smith, Peter
Abstract: Standard disc diffusion and MIC test procedure were used to investigate the susceptibility of two hundred and fifty‐one isolates collected from infected fish in France to florfenicol, oxolinic acid and tetracycline. The tests were performed at 22 ± 2℃ and for the 177 Yersinia rucker i they were read after 24–28 hr incubation and for the 74 Aeromonas salmonicida isolates they were read after 44–48 hr. Applying epidemiological cut‐off values to the susceptibility data generated in these tests, the isolates were categorized as wild‐type or non‐wild‐type. The agent‐specific categories into each isolate were placed on the basis of the data generated by the two methods were in agreement in 98% of the determinations made. It is argued that, with respect to categorising isolates, disc diffusion and MIC methods can be considered as equally valid at this temperature and after both periods of incubation.